Students' perception of the teaching ability of physical education, sports, and health - Ilmi, Mochamad; Roepajadi, Joesoef; Suroto, Suroto (Universitas Negeri Malang, 2024)
Background: Students' perception of teachers' abilities in teaching physical education and health sports is essential in improving the quality of physical education (PE) in schools. Understanding students' perceptions can be a foundation for improving teaching methods and motivating students to participate actively in physical activities. Objective: This study aims to determine students' perception of the teaching ability of physical education teachers at State Junior High School 1 Sidoarjo, East Java province, Indonesia. Methods: The research method used was a survey regarding students' perception of teachers' teaching ability. The instrument used in this study is the Formative Class Evaluation (FCE) questionnaire. This study involved 30 students. Qualitative and quantitative analysis to comprehensively understand students' perception of the ability to teach physical education and health sports subjects. Result: The results of the student assessment of PE teachers at State Junior High School 1 Sidoarjo through the overall FCE questionnaire from the indicators include a sizeable average result of 3.00, an average volition indicator of 2.83, an average method indicator of 2.57, while a cooperation indicator of the average is 2.60. With these results, the average overall student assessment of PE teachers of State Junior High School 1 Sidoarjo is 2.78, with a standard score of 5, and is included in the excellent category. Conclusion: This research concludes that a PE teacher assessment instrument is needed to implement learning to determine how PE teachers carry out the learning process for their students.